ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN CONSUMER GOODS DI BURSA EFEK INDONESIA PERIODE 2013-2017 PENGUJIAN PECKING ORDER THEORY - Novia Utami (Prosiding Working Papers Series In Management, 2018)
This research focuses on the pecking order theory by taking a sample of 100 consumer goods companies listed on the Indonesia Stock Exchange with the observation year 2013 to 2017. The purpose of this study is to see if there is consistency of research, as well as the previous studies to answer the research gap of extended pecking order theory model to see the effects of internal funding deficit and the debt ratio to the addition of forming internal funding deficit (dividends payment, additional working capital, investment and net cash flow) for additional debt ratio that can be used as a factor affecting changes in capital structure. The final results in this study support the hypothesis that the entire internal funding deficit has a positive effect on additional debt ratio. Dividend payments, additional working capital and investment have a positive effect while the net cash flow has a negative effect on the addition of the debt ratio. So the company can be said to support the pecking order theory. Keywords: pecking order, capital structure, internal funding deficit, dividend payments, additional working capital, investment, net cash flow.